Expression of Class II Human Leukocyte Antigens on Human Endothelial Cells Shows High Interindividual and Intersubclass Heterogeneity. Issue 5 (9th May 2023) - Béland, Stéphanie; Désy, Olivier; El Fekih, Rania; Marcoux, Meagan; Thivierge, Marie-Pier; Desgagné, Jean-Simon; Latulippe, Eva; Riopel, Julie; Wagner, Eric; Rennke, Helmut G.; Weins, Astrid; Yeung, Melissa; et al.
Abstract : Abstract : Significance Statement: Donor-specific antibodies against class II HLA are a major cause of chronic kidney graft rejection. Nonetheless, some patients presenting with these antibodies remain in stable histological and clinical condition. This study describes the use of endothelial colony-forming cell lines to test the hypothesis of the heterogeneous expression of HLA molecules on endothelial cells in humans. Flow cytometry and immunofluorescence staining revealed substantial interindividual and interlocus variability, with HLA-DQ the most variable. Our data suggest that the expression of HLA class II is predicted by locus. The measurement of endothelial expression of HLA class II in the graft could present a novel paradigm in the evaluation of the alloimmune risk in transplantation and certain diseases. Background: HLA antigens are important targets of alloantibodies and allospecific T cells involved in graft rejection. Compared with research into understanding alloantibody development, little is known about the variability in expression of their ligands on endothelial cells. We hypothesized individual variability in the expression of HLA molecules. Methods: We generated endothelial colony forming cell lines from human peripheral blood mononuclear cells ( n =39). Flow cytometry and immunofluorescence staining were used to analyze the cells, and we assessed the relationship between HLA-DQ expression and genotype. Two cohorts of kidney transplant recipients were analyzed to correlate HLA-DQ mismatches with the extent of intragraft microvascular injury. Results: Large variability was observed in the expression of HLA class II antigens, not only between individuals but also between subclasses. In particular, HLA-DQ antigens had a low and heterogeneous expression, ranging from 0% to 85% positive cells. On a within-patient basis, this expression was consistent between endothelial cell colonies and antigen-presenting cells. HLA-DQ5 and -DQ6 were associated with higher levels of expression, whereas HLA-DQ7, -DQ8, and -DQ9 with lower. HLA-DQ5 mismatches among kidney transplant recipients were associated with significant increase in graft microvascular. Conclusion: These data challenge the current paradigm that HLA antigens, in particular HLA class II, are a single genetic and post-translational entity. Understanding and assessing the variability in the expression of HLA antigens could have clinical monitoring and treatment applications in transplantation, autoimmune diseases, and oncology.